Features of the generation of fast particles from microstructured targets irradiated by high intensity, picosecond laser pulses. (June 2019) - Sedov, M.V.; Faenov, A.Ya.; Andreev, A.A.; Skobelev, I.Yu.; Ryazantsev, S.N.; Pikuz, T.A.; Durey, P.; Doehl, L.; Farley, D.; Baird, C.D.; Lancaster, K.L.; Murphy, C.D.; et al.
Abstract: The use of targets with surface structures for laser-driven particle acceleration has potential to significantly boost the particle and radiation energies because of enhanced laser absorption. We investigate, via experiment and particle-in-cell simulations, the impact of micron-scale surface-structured targets on the spectrum of electrons and protons accelerated by a picosecond laser pulse at relativistic intensity. Our results show that, compared with flat-surfaced targets, structures on this scale give rise to a significant enhancement in particle and radiation emission over a wide range of laser–target interaction parameters. This is due to the longer plasma scale length when using micro-structures on the target front surface. We do not observe an increase in the proton cutoff energy with our microstructured targets, and this is due to the large volume of the relief.